Death, graveyards and funerary architecture in Islamic civilization - Spahic, Omer (AS Noordeen, 2008)
If we were to examine the subject of funerary architecture in Islamic civilization, we would come face-to-face with some crucial and extremely difficult questions yet to be comprehensively answered in light of the Islamic worldview, as well as in light of an unprejudiced investigation of the cultures and civilization of the Muslim peoples. Some of such questions are: 1. How could the phenomenon of architecturally glorifying the dead become a widespread phenomenon among the Muslims when the Prophet (pbuh) and the first two exemplary generations of the Muslims sternly rejected it, in both words and deeds? 2. What were the root causes of the institution of Muslim funerary architecture? 3. Why did the grave of the Prophet (pbuh), and the graves of his two closest companions: Abu Bakr and Umar b. al-Khattab, end up incorporated into the Prophet’s mosque proper? Did this occurrence -- when all’s said and done -- have any implications for the introduction of Muslim funerary architecture? 4. Once grave-veneration and building over graves started emerging, what was the reaction/position of the religious and intellectual leadership? 5. When exactly did the whole thing start? 6. Did funerary architecture enjoy widespread authorization? 7. Why do Muslims build no shrines, mausoleums and memorials today -- with the exception of some extremely rare instances whereby no impact whatsoever is created on the general Muslim conscience? This book aims to cast some light on the theme of Muslim funerary architecture, thus attempting to render the answers on some crucial questions often asked about it. The book focuses on the origins, roles and significance of funerary architecture in Islamic civilization. It follows that discussing the plans and structural designs of funerary structures is not a focus in the book. The topics discussed are divided into five chapters entitled: Death in Islam; Visiting Graves; The Prophet Muhammad’s Grave; The Birth of Funerary Architecture in Islamic Civilization; The Reasons for the Institution and Proliferation of Funerary Architecture in Islamic Civilization.